P057: Evidence-based medicine (EBM) simulation: teaching real-time literature searching to emergency medicine residents using a flipped classroom and high-fidelity simulation. (May 2019) - Gray, I.; Dong, S.; Ha, D.
Abstract : Innovation Conept : Evidence-based medicine (EBM), including literature search skills, is an objective of the Emergency Medicine (EM) residency curriculum. Traditional teaching of this topic utilized a classroom-based, librarian-lead session that presented an overview of many search engines. Feedback from past sessions indicated that learners retained little after the session. To be effective, EBM needs to be brought to the bedside. We created a session to engage EM residents and improve their efficiency in literature searching during an EM shift.Methods : We conducted a needs assessment among EM residents in our program. In response to this and to maximize impact of teaching, we created an EBM workshop on literature searching that used a flipped classroom approach and high-fidelity simulation. The session was designed for a small group (12 junior residents), with the goals of being interactive, engaging and practice-relevant. Feedback was collected on the simulation experience.Curriculum, Tool or Material : With a librarian, we created a brief list of EM-relevant databases. It included tips for searching and links to the corresponding sites / apps. Students received the list 7 days prior and were instructed to set up the resources on their smartphones. Pre-readings also covered the hierarchy of evidence and formulating a good clinical (PICO) question. All students participated in the high-fidelity simulation, with one volunteer leader. The case involved a stable patient. Residents proceeded with initial case assessment until they faced a management decision that required a literature search. All residents participated on their smart phones. Collectively, it took 5 minutes to find a study that adequately addressed the clinical question. The patient was managed accordingly and symptoms resolved. Feedback on the simulation was abundantly positive. Students found it engaging, practical and realistic. It helped them learn to efficiently search the literature while managing a stable patient.Conclusion : Using a multi-modal teaching strategy that includes simulation makes teaching EBM literature searching more interesting, engaging and applicable to EM practice. Future work will look at creating further sessions to reinforce and promote retention of key concepts and integrate them into EM practice.